EXAMINING MUDHARABAH CONTRACTS IN PRIMA BERHADIAH TIME DEPOSIT PRODUCTS OF ISLAMIC BANKING THROUGH THE LENS OF MAQASHID SHARIA - Eny Latifah; Yuni Rohmah; Yusuf Yusuf (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to determine the implementation of the mudharabah contract on the Prima Prize Savings product at Bank Muamalat Indonesia KCP Lamongan and the maqashid sharia perspective on the implementation. The research method uses descriptive qualitative with the type of case study. The results of this study indicate that the implementation of the contract on Tabungan Prima Berhadiah at Bank Muamalat Indonesia KCP Lamongan uses a mudharabah muthlaqah contract. The maqashid sharia perspective on the implementation of the mudharabah contract on Savings Prima Berhadiah on five principles, namely protecting religion, protecting the soul, protecting the mind and mind, protecting property, and protecting offspring. The results shown in this study are the implementation of mudharabah contracts on Prima Berhadiah Savings products at Bank Muamalat Indonesia KCP Lamongan has been in accordance with the five principles of maqashid sharia.